Cyclosporine A Inhibits the T‐bet–Dependent Antitumor Response of CD8+ T Cells. Issue 4 (8th February 2016) - Rovira, J.; Renner, P.; Sabet‐Baktach, M.; Eggenhofer, E.; Koehl, G. E.; Lantow, M.; Lang, S. A.; Schlitt, H. J.; Campistol, J. M.; Geissler, E. K.; Kroemer, A.
Abstract : Transplant recipients face an increased risk of cancer compared with the healthy population. Although several studies have examined the direct effects of immunosuppressive drugs on cancer cells, little is known about the interactions between pharmacological immunosuppression and cancer immunosurveillance. We investigated the different effects of rapamycin (Rapa) versus cyclosporine A (CsA) on tumor‐reactive CD8 + T cells. After adoptive transfer of CD8 + T cell receptor–transgenic OTI T cells, recipient mice received either skin grafts expressing ovalbumin (OVA) or OVA‐expressing B16F10 melanoma cells. Animals were treated daily with Rapa or CsA. Skin graft rejection and tumor growth as well as molecular and cellular analyses of skin‐ and tumor‐infiltrating lymphocytes were performed. Both Rapa and CsA were equally efficient in prolonging skin graft survival when applied at clinically relevant doses. In contrast to Rapa‐treated animals, CsA led to accelerated tumor growth in the presence of adoptively transferred tumor‐reactive CD8 + OTI T cells. Further analyses showed that T‐bet was downregulated by CsA (but not Rapa) in CD8 + T cells and that cancer cytotoxicity was profoundly inhibited in the absence of T‐bet. CsA reduces T‐bet–dependent cancer immunosurveillance by CD8 + T cells. This may contribute to the increased cancer risk in transplant recipients receiving calcineurin inhibitors. Abstract : The authors show that immunosuppressive treatment with cyclosporine A, but not rapamycin, decreases T‐bet expression in tumor‐reactive CD8+ T cells, which inhibits the immune response against developing melanomas in an antigen‐specific mouse model.